Assessment of Carotid Body Tumors by Superb Microvascular Imaging of Feeding Arteries During Preoperative Evaluation - Gao, Luying; Zhang, Xiaoyan; Jiang, Yuxin; Wang, Hongyan; Zheng, Yuehong; Li, Wanying; Li, Jianchu; Zhang, Bo (Frontiers in Surgery, 2022)
Superb microvascular imaging (SMI) has led to new advances in vascular imaging applications. This study aimed to explore the blood supply and feeding arteries of carotid body tumors (CBTs) on SMI to improve the accuracy of information available to surgeons. Twenty-six CBT lesions were subjected to color Doppler flow imaging (CDFI) and SMI and were later confirmed by pathology. The blood flow patterns and feeding arteries of the CBTs on CDFI and SMI were graded and compared. The feeding arteries of two CBT lesions, which were not visible on CDFI, were identified as the internal carotid artery (ICA) on SMI. The feeding arteries of three CBTs were judged to stem from both the ICA and the external carotid artery (ECA) (MIX) based on SMI compared to the ICA or ECA on CDFI. We classified the feeding arteries of CBTs as originating from the ICA or others (including the ECA and MIX). One hundred percent (3/3) of the CBT lesions stemming from the ICA had Adler I or Adler II blood flow patterns, and 100% (23/23) of the CBT lesions stemming from other arteries had Adler II or Adler III blood flow patterns. Higher Adler categories were assigned based on SMI than CDFI (P<0.001). In conclusion, SMI may be superior to CDFI in detecting the vascularity of CBTs, and SMI revealed more potential feeding arteries of CBTs than CDFI. CBTs originating from the ICA are less vascular than those originating from the ECA.